Women in Top management Role Models from around the Globe share their Paths to success - Al-Sadik-Lowinski, Bettina (De Gruyter, 2020)
Ask 110 top female executives from five nations to reflect on their careers and leadership as part of an international scientific study and you will uncover a set of recommendations for women who want to become and remain international business leaders. There is also invaluable advice for corporate managers wanting to recruit skilled women into executive positions. This book is based on the authentic experiences and original words of the interviewees - all of whom are senior female executives - and on the author's analytical insights, all set within a qualitative, scientific framework. In this international research project, the Global Women Career Lab, the author analyzes what motivates these fascinating role models, how they plan their career trajectories, what mechanisms they use to overcome obstacles and what leadership strategies have enabled these women to reach senior management positions. The book offers the reader a remarkable insight into the experiences of women in top business positions in Russia, China, Japan, France and Germany. About the author: Dr. Bettina-Al-Sadik-Lowinski is a researcher, author and certified international mentor-coach (MCC). Following a long management career in multinational companies, she has worked as an international executive coach and expert on diversity in Germany, France, Japan and China. Reviews: "A wealth of testimonials from female role models from all over the world, with valuable advices for women pursuing professional development as well as for companies leveraging diversity for competitive advantage."Hong Chow, China CEO Roche Pharma, Member of Supervisory Board Beiersdorf "Women need other women as role models in management in order to plan their careers more strategically and understand that the sky is unlimited for them. In this book, 110 role models from various countries share their experiences and I was especially impressed by the examples from Asian female leaders."Mari Nogami, President Takeda Consumer Healthcare Japan, Ex (the first) Chair of Women in Business AmCham Japan "As a big advocator for global diversity I recommend this book to all women who want to rise up their careers globally and to corporate leaders who support diversity in their companies worldwide!"Rosa Lee, Executive Vice President of Bosch China, Member of the Board and Corporate HR Head APAC "It's not right to think that business is a man´s world. Women are more sensitive and calmer - this makes us different, helps us to balance and makes ladies the best partners for men."Natalia Ryzhkova, CEO Gulliver&Co Int., Russia " International, authentic reports from female top managers from different countries combined with a sound scientific analysis of the growth factors for women in management. Insights across countries. Highly recommended!"Professor Dr. Jutta Rump, Managing Director, Institut of Employability (IBE), University of the Economy and Society Ludwigshafen, Germany "Women need to understand the country specific codes and create their best image as topmanager- using language, their look and body postures. This books shows us the similarities and the differences of female images in top positions in the five nations. Great findings!"Muriel de Saint Sauveur, President Women Masterclass France, former International Marketing, Communications and Diversity Director, Mazars Group, France "Les femmes doivent oser prendre leur juste place dans l'economie, que ce soit en tant qu'entrepreneure ou en tant que cadre dirigeante. C'est une question d'equilibre social mais plus encore de potentiel de performance. Plus de femmes signifie plus de croissance et plus de diversité dans les choix stratégiques. Osez, osez, c'est le maitre-mot à mettre en pratique!"Marie-Claire Capobianco, Ex membre du Comité exécutif du groupe BNPParibas, Membre du Haut Comité de Gouvernement d'Entreprise, France "Chinese female executives have many strengths. Great learnings also from women around the world. A treasure book!"Shelley Chen, Senior Director Human Resources, Communications and Public Relations, Saint-Gobain Pipe, APAC, Head of PAM-LAN- Diversity Institute, China " Top managers from five nations provide insights into how they strategically plan their careers, and break down barriers. The author Dr. Bettina AL-Sadik-Lowinski has managed to work out the cultural differences and similarities between these women. Very educational, worth reading and scientifically sound."Prof. Manuela Rousseau, Deputy chairwoman of the supervisory board and Author, Germany " Finally. International role models report what women need to advance further. The "es contain a global fund that helps women successfully overcome barriers."Christine Rittner, former Global CHRO, Executive board member, Lidl, Germany " A journey through the career worlds of women of different cultures. Solidarity from women for women. Highly recommended." Dr. Marion Welp, Attorney at Law, Chief Human Resources & Legal Affairs Officer, Member Executive Management Team, Board member, Esprit, Germany "Women in top management positions speak plain language. A great initiative. "Sonja Mechling, Head of Global Marketing, UX & Digital Innovation, Schindler Group, Germany "This world deserves more ladies in the leadership positions as a driver of positive changes. Dr. Bettina and her ladies had found their way to the Top and generously shares it in the book."Evgeny Bazhov, Chief Representative, Russia, Financial Association of EuroAsian Cooperation "Full of valuable insights. A must read to understand how women career paths work. Read it. Implement it."Christine Hesse, CEO Hesse Design, Germany.